THE IMPLEMENTATION OF AUTHENTIC ASSESSMENT ON AKIDAH AKHLAK SUBJECT OF THE 5th GRADE IN MIS MAKKARAENG MAROS - Nurhadijah, Nurhadijah; Ibrahim, Misykat Malik; Saprin, Saprin; Arif, Muhammad (Program Pascasarjana, UIN Alauddin Makassar, 2022)
This study aims to describe the implementation of authentic assessment in Akidah Akhlak subject. Sub problem, i.e., 1). How is the authentic assessment process on the 5th grade of Akidah Akhlak subject at MIS Makkaraeng Maros? 2). How are the authentic assessment results on the 5th grade of Akidah Akhlak subject at MIS Makkaraeng Maros?? This type of research is descriptive qualitative research—the data collection is from two primary and secondary sources. The research method used interviews, observation, and documentation, while the data analysis techniques consisted of data reduction, presentation, and verification. The data validity technique is in the form of a triangulation technique. The results showed: (1) The implementation of authentic research in the Akidah Akhlak subject at MIS Makkaraeng Maros went well in the authentic assessment process, which prepared the assessment plan, carried out the assessment, and then carried out the assessment process. (2) The results of the authentic assessment have been carried out in three domains, namely knowledge competence (cognitive), attitude competence (affective), and skill competence (psychomotor). All forms of assessment on the cognitive aspect were already to the maximum. At the same time, we carried out the affective and psychomotor aspects, although only on the primary assessment technique. In contrast, supporting assessments, such as self-assessment, peer-to-peer assessment, portfolio assessment, and project assessment, have not been used by the teachers of Akidah Akhlak subject in the 5th grade at MIS Makkaraeng Maros. In conclusion, the Akidah Akhlak teacher has carried out value from the authentic assessment process with different steps in terms of attitudes, knowledge, and skills. This research implies that authentic assessment requires teachers to broaden their horizons and increase their knowledge to carry out authentic assessments with various assessment forms and many students.